The curvilinear associations between Life’s Crucial 9 and frailty: cross-sectional study of NHANES 2003 - 2023 - Wang, Bo; Jiang, Chunqi; Wang, Ning; Qu, Yinuo; Wang, Jun; Zhao, Guang; Zhang, Xin (Frontiers in Aging, 2025)
BackgroundFrailty not only affects disease survival rates but also the quality of life. The Life’s Crucial 9 (LC9) is a recently proposed cardiovascular health risk score that incorporates mental health along with Life’s Essential 8 (LE8). The association between LC9 and frailty has not yet been reported. This study aims to explore the link between LC9 scores and levels of frailty.MethodsWe used a weighted multiple logistic regression model to evaluate the relationship between Life’s Essential 8 (LE8) and LC9 with frailty, and conducted trend tests to assess the stability of this association. Additionally, we employed smooth curve fitting to explore the potential curvilinear relationship between LE8 and LC9 with frailty. To identify inflection points, we applied recursive partitioning algorithms in conjunction with a two-stage linear regression model. Stratified analyses were performed to examine heterogeneity within various populations.ResultsOur study included a total of 28,557 participants. In the regression model that accounted for all covariates, the odds ratios (ORs) for the association of LE8 and LC9 scores with frailty were 0.95 (95% CI: 0.94, 0.95) and 0.93 (95% CI: 0.93, 0.93), respectively, indicating a significantly stronger negative correlation with LC9 scores. Sensitivity analysis confirmed the robustness of this relationship. Smooth curve fitting revealed a nonlinear correlation between LE8 and LC9 scores and the degree of frailty. Further analysis using a two-piecewise linear regression model identified inflection points at 53.12 for LE8 and 68.89 for LC9. Below these thresholds, both LE8 and LC9 demonstrated a significant negative association with frailty. However, above these points, the strength of the negative correlation was somewhat reduced but remained statistically significant. In stratified analyses, both LE8 and LC9 exhibited significant negative associations with frailty, with LC9 showing a more pronounced relationship. Significant interaction effect was detected within the education level groups.ConclusionWe found a curvilinear relationship between LE8, LC9 and frailty, and the relationship between LC9 and frailty was more significant. This implies that LC9 can facilitate the early and precise identification of individuals at high risk of frailty, thereby providing a foundation for the development of targeted intervention strategies.